The Influence Of Auditor Competency, Independence, And Professional Ethics On Audit Quality In Public Accounting Firm In Medan - Ahmad Muhajir; Ferry Safriandi; Habibah Rahayu Nasution (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
The aim of this study is to determine the influence of Competence, Independence and Professional Ethics Auditors' Impact on Audit Quality at Public Accounting Firms in Medan. This research is a This type of research is casual and is a replica of previous research with the research population. are auditors who work at a public accounting firm in Medan. In this study, the population obtained from the Public Accounting Office in Medan, as many as 160 auditors. The sample in this study selected based on convenience sampling. The sample was obtained from the Public Accounting Office in Medan in 2024 had 54 auditors. The sample data used was primary data. Namely data that comes from the original or first source. The data analysis technique used is descriptive statistical analysis methods, classical assumption tests, and multiple linear regression tests. The results of this study concluded that partially Competence and Independence have a positive and significant influence on Audit Quality. However, Auditor Professional Ethics does not have a significant effect on Audit Quality. Audit. Then simultaneously the Auditor's Competence, Independence and Professional Ethics are influenced significant effect on Audit Quality with a significant value of 0.000 < 0.05 at the Accounting Firm Public in Medan.